A study comparing depression, anxiety, and coping styles between high school students attending and not attending coaching class for medical entrance examination - Krishan Kumar Sharma; Parth Singh Meena; Charan Singh Jhilowa; Shubham Jhanwar; Jitendra Rohilla; Pinki Tak; Mahendra Jain (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Various kinds of stressors and psychological problems have been reported in the adolescent student population. This study assessed and compared depression, anxiety, and various coping styles among high school students attending coaching classes for medical entrance examination (MEE) and those not. MATERIALS AND METHODS: Systemic random sampling technique was used to recruit 400 high school students with equal number of those attending (Group 1) and those not attending any coaching class for MEE (Group 2). They underwent screening for depression and anxiety through Patient Health Questionnaire-9 and Generalized Anxiety Disorder 7-item. Coping styles were assessed through brief COPE inventory. Screening positive subjects were assessed in detail by a psychiatrist using ICD-10 (International Classification of Diseases 10th Revision), Diagnostic Criteria for Research (DCR). The severity of depression and anxiety was measured through HAM-D and HAM-A, respectively. RESULTS: Depression and anxiety were reported by higher proportion of Group 1 (36%) than Group 2 (22%), χ2 (1) = 9.52; P = 0.002. In both the groups, depressive disorder was the most common, followed by generalised anxiety-disorder and mixed anxiety-depression. The severity of depression (HAM-D score) and anxiety (HAM-A Score) was significantly more Group 1. "Active coping" (χ2 = 4.79 P = 0.02) and "Humor" (χ2 = 30.90, P ≤ 0.01) were more commonly used by healthy students, while "Religious coping" (χ2 = 37.92 P ≤ 0.01) were the most common among those diagnosed with depression/anxiety disorder. CONCLUSION: Higher prevalence of the psychological problems in adolescent school students preparing for MEE highlights the importance of aptitude assessment, career counseling, and school mental health program before their exposure to the competitive academic atmosphere.